THE IMPACT OF GEMINI AI ON STUDENTS' WRITING PERFORMANCE - Rizki Bobi Baihaki; Melinah Diana Putri; Naf’an Tarihoran (CV. Denasya Smart Publisher, 2026)
The integration of Artificial Intelligence (AI) in education offers transformative potential, yet EFL learners still face significant hurdles in writing proficiency. This study aims to explore the effectiveness of Google Gemini, a multimodal Large Language Model (LLM), in enhancing students' writing performance and overcoming psychological barriers, such as low motivation. Using a qualitative approach grounded in the Technology Acceptance Model (TAM) and Socio-constructivism theory, this research examines how Gemini's real-time feedback functions as a